Investigation of the tensile strength of bending in building plasters with silica fumes - Yildiz, Servet; Yalinbaş, Muhammed; Keleştemur, O?uzhan (My University, 2005)
In this study, the usability of building plasters with silica fumes which is held in the Etibank Electro-metallurgy company-Antalya, is examined. The samples obtained from the result of displacement with specified proportions (5, 10, 15, 20, 25%) of the control sample as volumetric, papier-meché and SiFeCr chimney dust which are prepared beforehand are mixed. Then, the obtained samples are compared with the control sample_in terms of the unit weight, porosity and bending strength. When adding silica fume to the mixture, water requirement is increased. Therefore, water addition has been completed in the amount of silica fume. Thus, it does not need for using the super-plastificiser addition material. In the condition of using silica fume, the consequence of comparisons which is done with the control samples, is determined that porosity and unit weights of them decrease whereas the bending strength of them increases. As a conclusion, it is seen that the best results are obtained on the condition that the average amount of displacement with SiFeCr chimney dust and plaster is 10-15%.
Si?li?s dumani katkili yapi alçilarinda e?i?lmede çekme dayaniminin araştirilmasi
Keywords: Amount of cavity; Bending strength; Plaster; Silica fume; Unit weight